INFLUENCE OF FIRM CHARACTERISTICS ON LOAN APPROVAL FOR SMEs IN NORTH CENTRAL NIGERIA: BANKERS’ PERCEPTION - Lukman Adebayo Oke; Yusuf Olamilekan Quadri; Daud Omotosho Saheed (Malete Journal of Accounting and Finance)
The scourge of paucity of finance to SMEs which has been undermining their potential as drivers of economic growth has been blamed partly on firm related characteristics. However, the fact that little has been done in this regard from the supply side (banks) spurs this research. This study investigates the influence of firm specific characteristics on loan approval for SMEs in North Central Nigeria. Data was drawn from the primary source through the use of questionnaires to elicit responses from the sampled bank loan officers in the study area. A sample of 207 was drawn from the volunteer loan officers in 448 branches using multistage sampling technique. Descriptive statistics and Kruskal Wallis H were employed in analyzing the data. The study found that all the identified firm characteristics (size, age, incorporation, industry, financial information, location and collateral), which are all significant at 0.01 but with varying degrees, are the factors influencing banks’ credit approval for SMEs in the North Central Nigeria. The study concluded that while banks attach greater importance to firm size, firm age and location in their loan decision for SMEs, they also give consideration though lesser, to other factors. The study thus recommended among others, the need for SMEs to synergize and borrow as consortium rather than as individual units. This will facilitate improved financial access and economies of scale in terms of relatively reduced loan costs. Similarly, SMEs should also consider setting up urban offices to achieve close proximity to their banks for better financial access.